Diets Rich in Olive Oil, Palm Oil, or Lard Alter Mitochondrial Biogenesis and Mitochondrial Membrane Composition in Rat Liver. (21st February 2022) - Djohan, Youzan Ferdiand; Camara-Cissé, Massara; Fouret, Gilles; Bonafos, Béatrice; Jover, Bernard; Cristol, Jean-Paul; Coudray, Charles; Feillet-Coudray, Christine; Badia, Eric
Abstract : Palm oil (crude or refined) and lard are rich in SFA, while olive oil is rich in polyunsaturated fatty acids. SFA are considered harmful to health, while polyunsaturated fatty acids are beneficial to health. The aim of this study was to determine the effect of diets rich in crude PO, refined PO, OO, or lard on the mitochondrial membrane, the activity of mitochondrial respiratory chain complexes, and mitochondrial biogenesis. This was an experimental study in male Wistar rats fed a diet containing 30% of each oil. Rats had free access to food and water. After being fed for 12 weeks, animals were sacrificed and liver mitochondria were collected. This collection was used to determine membrane potential and ROS production, membrane phospholipid and fatty acid composition, citrate synthase activity and respiratory chain complex, cardiolipin synthase protein expression, and expression of selected genes involved in mitochondrial biogenesis. We found that diets rich in olive oil, palm oil, or lard altered mitochondrial biogenesis by significantly decreasing Pgc1 α gene expression and altered the fatty acid composition of rat liver mitochondrial membrane PL.